Implementasi Alat Pelindung Diri Sebagai Esensi K3 Pada Pekerja Las Konstruksi di UMKM - Rian Prasetyo; Rahmatul Ahya; Mathilda Sri Lestari; Ainur Komariah (Journal of Appropriate Technology for Community Services, 2024)
Occupational safety and health (K3) is very important. There are various types and levels of employment sectors in Indonesia, one of which is in the MSME (Micro, Small and Medium Enterprises) sector which is engaged in the welding service sector. Based on observations made at UMKM "Bintang Jaya Steel", there are many conditions that are quite dangerous to the K3 of workers, because workers carry out welding processes and other work, without using PPE. Some workers also show a lack of understanding regarding the use of PPE in the welding process. This is certainly contrary to the importance of implementing K3 in this type of work. This Community Service activity is carried out with the aim of solving existing problems with partners. So far the partners do not fully know the legal basis for OSH and all the PPE needed for welding work, especially in construction work. The service is carried out by providing socialization and procuring PPE for construction welding work at these MSMEs. The results of this activity can be in accordance with the plan. This is shown from the evaluation and discussion results, where supervisors as well as MSME owners and operators can apply the use of PPE in construction welding work.